Relationship between the G894T polymorphism (Glu298Asp variant) in endothelial nitric oxide synthase and nitric oxide-mediated endothelial function in human atherosclerosis. - Guzik, T; Black, E; West, N; McDonald, D; Ratnatunga, C; Pillai, R; Channon, K (2001)
Nitric oxide (NO), produced by endothelial nitric oxide synthase (eNOS), plays important roles in normal vascular homeostasis, and reduced endothelial NO bioactivity is an important feature of vascular disease states. The Glu298Asp (G894T) polymorphic variant of eNOS has been associated with vascular disease, but functional data are lacking. Accordingly, we examined the relationships between NO-mediated endothelial function, the presence of the eNOS Glu298Asp variant, and clinical risk factors for atherosclerosis. Endothelium-dependent vasorelaxations to different agonists were determined in human saphenous veins obtained from patients with coronary artery disease and identified risk factors (n = 104). Patients were genotyped for the eNOS G894T polymorphism. Nitric oxide-mediated endothelial vasorelaxations were highly variable between patients. Reduced vasorelaxations were associated with increased number of clinical risk factors for atherosclerosis (r = - 0.54, P < 0.001), whereas the Glu298Asp variant was not associated with any differences in contractions to phenylephrine, NO-mediated vasorelaxations to acetylcholine, bradykinin or calcium ionophore, or relaxations to the NO donor sodium nitroprusside. Increased atherosclerotic risk factors, but not the presence of the eNOS Glu298Asp variant, are associated with impaired nitric oxide-mediated endothelial vasomotor function, suggesting that this polymorphism does not have a major direct functional effect on vascular eNOS activity in human atherosclerosis.